Sharia Insurance Agents’ Strategies in Responding to Digital Transformation: a Study at PT. Prudential Sharia Life Assurance - Alkautsar Malau, Ridho; Syahbudi, Muhammad; Imsar, Imsar (IAIN Manado, 2025)
The Indonesian sharia insurance industry faces significant challenges due to the phenomenon of creative destruction in the era of digital transformation. This study examines the strategies employed by agents of PT. Prudential Sharia Life Assurance, Binjai Branch, in addressing business changes triggered by digitalization, the decline in the number of policies issued, and fluctuations in premium income. The research method used the Technology Acceptance Model (TAM) approach, with data collected through questionnaires distributed to agents. The results indicate that the public's low understanding of digital sharia insurance and agents' limited ability to utilize digital technology are the main obstacles to market penetration and customer education. The company's digital infrastructure, including the data management system and Pruforce digital platform, has not been optimally integrated, thus hampering effective service delivery. A digital strategy that emphasizes strengthening the role of agents as financial consultants and the use of digital platforms has positive potential to improve marketing and service effectiveness. The success of digital transformation depends heavily on the readiness of human resources who master technology and the principles of sharia insurance. Therefore, it is recommended to develop digital infrastructure, provide ongoing training for agents, educate the public about sharia insurance, and collaborate with digital platforms and social media to expand the market and maintain the company's competitiveness.